A Clinical and Animal Experiment Integrated Platform for Small-Molecule Screening Reveals Potential Targets of Bioactive Compounds from a Herbal Prescription Based on the Therapeutic Efficacy of Yinchenhao Tang for Jaundice Syndrome. (September 2021) - Xiong, Hui; Zhang, Ai-Hua; Guo, Ya-Jing; Zhou, Xiao-Hang; Sun, Hui; Yang, Le; Fang, Heng; Yan, Guang-Li; Wang, Xi-Jun
Abstract: A herbal prescription in traditional Chinese medicine (TCM) has great complexity, with multiple components and multiple targets, making it extremely challenging to determine its bioactive compounds. Yinchenhao Tang (YCHT) has been extensively used for the treatment of jaundice disease. Although many studies have examined the efficacy and active ingredients of YCHT, there is still a lack of an in-depth systematic analysis of its effective components, mechanisms, and potential targets—especially one based on clinical patients. This study established an innovative strategy for discovering the potential targets and active compounds of YCHT based on an integrated clinical and animal experiment platform. The serum metabolic profiles and constituents of YCHT in vivo were determined by ultra-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UPLC-Q-ToF-MS)-based metabolomics combined with a serum pharmacochemistry method. Moreover, a compound–target–pathway network was constructed and analyzed by network pharmacology and ingenuity pathway analysis (IPA). We found that eight active components could modulate five key targets. These key targets were further verified by enzyme-linked immunosorbent assay (ELISA), which indicated that YCHT exerts therapeutic effects by targeting cholesterol 7α-hydroxylase (CYP7A1), multidrug-resistance-associated protein 2 (ABCC2), multidrug-resistance-associated protein 3 (ABCC3), uridine diphosphate glucuronosyl transferase 1A1 (UGT1A1), and farnesoid X receptor (FXR), and by regulating metabolic pathways including primary bile acid biosynthesis, porphyrin and chlorophyll metabolism, and biliary secretion. Eight main effective compounds were discovered and correlated with the key targets and pathways. In this way, we demonstrate that this integrated strategy can be successfully applied for the effective discovery of the active compounds and therapeutic targets of an herbal prescription.